2019
DOI: 10.3390/medicina55090530
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain Patients’ Gaze Patterns toward Pain-Related Information: Comparison between Pictorial and Linguistic Stimuli

Abstract: Background and Objectives: The attentional bias and information processing model explained that individuals who interpret pain stimuli as threatening may increase their attention toward pain-related information. Previous eye tracking studies found pain attentional bias among individuals with chronic pain; however, those studies investigated this phenomenon by using only one stimulus modality. Therefore, the present study investigated attentional engagement to pain-related information and the role of pain catas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Moreover, attentional avoidance from pain-related information was also not observed for the high pain catastrophizing group during the later stage of attention. A previous study (Lee et al, 2019) that utilized similar research methods also found non-significant effects of pain catastrophizing on attentional bias to pain facial expressions. As discussed earlier, this result may be due to the fact that chronic pain patients' experience of outpatient hospital-based treatment alters their attentional patterns to pain facial expressions.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Moreover, attentional avoidance from pain-related information was also not observed for the high pain catastrophizing group during the later stage of attention. A previous study (Lee et al, 2019) that utilized similar research methods also found non-significant effects of pain catastrophizing on attentional bias to pain facial expressions. As discussed earlier, this result may be due to the fact that chronic pain patients' experience of outpatient hospital-based treatment alters their attentional patterns to pain facial expressions.…”
Section: Discussionmentioning
confidence: 63%
“…The result of the current study did not support the evidence for the attentional bias to pain facial expressions among chronic pain patient group. Previous research has found consistent evidence for the attentional bias to pain words but not for facial expression stimuli (Lee et al, 2019;Mazidi et al, 2019). It may be that facial expression stimuli are not as relevant to chronic pain patients' pain experiences as photos of affected areas or pain word stimuli.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations